Training course in point-of-care ultrasound in the urgency and emergency study of the undergraduate medical education - Luiza Fleury de F. Serruya; Yuri Aarão A. Serruya; Ariney Costa de Miranda; Cláudio Eduardo C. Teixeira (Educación Médica)
Objective: Train undergraduate medical students to practice point-of-care ultrasound (POCUS) in the urgency and emergency module of the medical internship. Methods: The study was carried out through the Extended Focused Assessment with Sonography in Trauma theoretical–practical ultrasonography course applied to students in the 11th semester of the CESUPA medical course. Results: It was found that most university students demonstrated an improvement in their ability to carry out and grasp knowledge about the subject after applying theoretical and practical classes on an ultrasound device and ultrasound training simulator. Conclusion: The improvement in student performance after the practical activity encourages discussion about the importance of curricular adjustment to adapt to technological advances in the medical field. Resumen: Objetivo: Capacitar a estudiantes de pregrado de medicina para la práctica de ultrasonido básico a pie de cama en el módulo de Urgencia y Emergencia del internado médico. Métodos: El estudio se realizó a través del Curso de Ultrasonografía Teórico-Práctico E-FAST aplicado a estudiantes del undécimo semestre de la carrera de medicina del CESUPA. Resultados: Se encontró que la mayoría de los estudiantes universitarios demostraron una mejora en su capacidad para realizar y captar conocimientos sobre el tema luego de aplicar clases teóricas y prácticas en un ecógrafo y simulador de entrenamiento en ultrasonido. Conclusión: La mejora en el rendimiento de los estudiantes luego de la actividad práctica propicia la discusión sobre la importancia del ajuste curricular para adaptarse a los avances tecnológicos en el campo médico.